Claudin peptidomimetics modulate tissue barriers for enhanced drug delivery. Issue 1 (15th May 2017) - Dithmer, Sophie; Staat, Christian; Müller, Carolin; Ku, Min‐Chi; Pohlmann, Andreas; Niendorf, Thoralf; Gehne, Nora; Fallier‐Becker, Petra; Kittel, Ágnes; Walter, Fruzsina R.; Veszelka, Szilvia; Deli, Maria A.; et al.
Abstract : The blood–brain barrier (BBB) formed by the microvascular endothelium limits cerebral drug delivery. The paraendothelial cleft is sealed by tight junctions (TJs) with a major contribution from claudin‐5, which we selected as a target to modulate BBB permeability. For this purpose, drug‐enhancer peptides were designed based on the first extracellular loop (ECL) of claudin‐5 to allow transient BBB permeabilization. Peptidomimetics (C5C2 and derivatives, nanomolar affinity to claudin‐5) size‐selectively (≤40 kDa) and reversibly (12–48 h) increased the permeability of brain endothelial and claudin‐5–transfected epithelial cell monolayers. Upon peptide uptake, the number of TJ strand particles diminished, claudin‐5 was downregulated and redistributed from cell–cell contacts to the cytosol, and the cell shape was altered. Cellular permeability of doxorubicin (cytostatic drug, 580 Da) was enhanced after peptide administration. Mouse studies (3.5 μmol/kg i.v.) confirmed that, for both C5C2 and a d‐amino acid derivative, brain uptake of Gd–diethylene‐triamine penta‐acetic acid (547 Da) was enhanced within 4 h of treatment. On the basis of our functional data, circular dichroism measurements, molecular modeling, and docking experiments, we suggest an association model between β‐sheets flanked by α‐helices, formed by claudin‐5 ECLs, and the peptides. In conclusion, we identified claudin‐5 peptidomimetics that improve drug delivery through endothelial and epithelial barriers expressing claudin‐5.